Human metapneumovirus: a new respiratory pathogen - Broor, S. (J Biosci, 2008)
Human metapneumovirus is a recently recognized pathogen of acute respiratory tract infection (ARI) in children as well as elderly and immunocompromised adults. The virus belongs to the family Paramyxoviridae, sub family Pneumovirinae and genus Metapneumovirus. Through genetic analysis it has been characterized into two groups A and B which are further divided into four sub-lineages. The virus is difficult to grow in tissue culture and hence reverse transcriptase-polymerase chain reaction (RT-PCR) for N and L gene is the method of choice for diagnosis. The virus has been seen in all countries with seasonal distribution in winter months for temperate and spring/summer for tropical countries. F gene is the most conserved among different lineages and efforts are underway to design recombination vaccine using F gene.